SIRT1 Activity in Peripheral Blood Mononuclear Cells Correlates with Altered Lung Function in Patients with Chronic Obstructive Pulmonary Disease. (9th May 2018) - Conti, Valeria; Corbi, Graziamaria; Manzo, Valentina; Malangone, Paola; Vitale, Carolina; Maglio, Angelantonio; Cotugno, Roberta; Capaccio, Damiano; Marino, Luigi; Selleri, Carmine; Stellato, Cristiana; Filippelli, Amelia; et al.
Abstract : Background . Oxidative stress is a recognized pathogenic mechanism in chronic obstructive pulmonary disease (COPD). Expression of the NAD + -dependent deacetylase Sirtuin 1 (SIRT1), an antiaging molecule with a key role in oxidative stress response, has been described as decreased in the lung of COPD patients. No studies so far investigated whether systemic SIRT1 activity was associated to decreased lung function in this disease. Methods . We measured SIRT1 protein expression and activity in peripheral blood mononuclear cells (PBMCs) and total oxidative status (TOS), total antioxidant capacity (TEAC), and oxidative stress index (TOS/TEAC) in the plasma of 25 COPD patients, 20 healthy nonsmokers (HnS), and 20 healthy smokers (HS). Results . The activity of SIRT1 was significantly lower in COPD patients compared to both control groups while protein expression decreased progressively (HnS > HS > COPD). TOS levels were significantly lower in HnS than in smoke-associated subjects (COPD and HS), while TEAC levels were progressively lower according (HnS > HS > COPD). In COPD patients, SIRT1 activity, but not protein levels, correlated significantly with both lung function parameters (FEV1/FVC and FEV1) and TEAC. Conclusions . These findings suggest loss of SIRT1-driven antioxidant activity as relevant in COPD pathogenesis and identify SIRT1 activity as a potential convenient biomarker for identification of mild/moderate, stable COPD.